PREPARING HUMAN RESOURCES WITH AFFORDABLE COST - admin admin; Mashudi Mashudi (Proceedings of The ICECRS, 2016)
Coming from the experience of living in two different situations, namely in the area of subcultures of Mataraman from birth up to adults, and further, when one is married, he lives in a subculture arek or coastal area. At this stage, it was found that there are two different phenomena regarding socioeconomic dimension. In the area of subculture Mataraman, the socioeconomic level of parents is low, but it has ahigher level of formal education of the children. In contrast, while in coastal areas, thesocio-economic level of parents is high but has alowerlevel of the children’s formal education.In response to this gap, the author attempts toanswer the question "To what extent culture affect the educational achievement of children?". The finding of thepresent study showed that the higher the cultural dimension of the parents, the higher the level of educational achievement of children.